Determination of the fibre content and orientation in UHPFRC layers using NDT - application to the simulation of the behaviour of strengthened beams - Mário Jorge Pimentel (2016)
An experimental study on beams failing in bending is presented. Eight beams were tested, 4 of them reinforced with a 50mm thick ultra-high performance fibre reinforced cement-based composite (UHPFRC) layer. The tested beams reproduce the behaviour of one-way slabs in the hogging moment region, without shear reinforcement in the test span. An NDT method based on the magnetic properties of the steel fibres is adopted for determining two reliable indicators of the fibre content and fibre orientation within the strengthening layer. It is shown that these two indicators can be directly correlated to the parameters of a simple mechanical model providing the tensile strength of the composite. The UHPFRC tensile constitutive law used for modelling the structural response of the strengthened beams is estimated from non-destructive measurements and it is shown that good agreement can be found. (c) 2016 Taylor & Francis Group, London.